Dual transcriptomic analysis reveals early induced Castanea defense-related genes and Phytophthora cinnamomi effectors - Fernandes, Patrícia; Pimentel, Diana; Ramiro, Ricardo S.; Silva, Maria do Céu; Fevereiro, Pedro; Costa, Rita Lourenço (Frontiers in Plant Science, 2024)
Phytophthora cinnamomi Rands devastates forest species worldwide, causing significant ecological and economic impacts. The European chestnut (Castanea sativa) is susceptible to this hemibiotrophic oomycete, whereas the Asian chestnuts (Castanea crenata and Castanea mollissima) are resistant and have been successfully used as resistance donors in breeding programs. The molecular mechanisms underlying the different disease outcomes among chestnut species are a key foundation for developing science-based control strategies. However, these are still poorly understood. Dual RNA sequencing was performed in C. sativa and C. crenata roots inoculated with P. cinnamomi. The studied time points represent the pathogen’s hemibiotrophic lifestyle previously described at the cellular level. Phytophthora cinnamomi expressed several genes related to pathogenicity in both chestnut species, such as cell wall–degrading enzymes, host nutrient uptake transporters, and effectors. However, the expression of effectors related to the modulation of host programmed cell death (elicitins and NLPs) and sporulation-related genes was higher in the susceptible chestnut. After pathogen inoculation, 1,556 and 488 genes were differentially expressed by C. crenata and C. sativa, respectively. The most significant transcriptional changes occur at 2 h after inoculation (hai) in C. sativa and 48 hai in C. crenata. Nevertheless, C. crenata induced more defense-related genes, indicating that the resistant response to P. cinnamomi is controlled by multiple loci, including several pattern recognition receptors, genes involved in the phenylpropanoid, salicylic acid and ethylene/jasmonic acid pathways, and antifungal genes. Importantly, these results validate previously observed cellular responses for C. crenata. Collectively, this study provides a comprehensive time-resolved description of the chestnut–P. cinnamomi dynamic, revealing new insights into susceptible and resistant host responses and important pathogen strategies involved in disease development.